Determination of suitable species combination of two small indigenous fish species (SIS) pabda (Ompok pabda) and gulsha (Mystus cavasius) with rohu (Labeo rohita) in farmers’ pond - Md Nahiduzzaman; Md Shahidul Islam; Shayla Sultana Mely; Md Moshiur Rahman; Md Robiul Awal; AHM Kohinoor (Research in Agriculture Livestock and Fisheries, 2023)
An experiment was carried out from May to September, 2018 to determine the suitable species combination of two indigenous fish Pabda (Ompok pabda) and Gulsha (Mystus cavasius) with Rohu in farmer’s pond. Three species combinations (% of total stocking densities) Gulsha: Pabda = 60: 40 at T1, 40: 60 at T2, and 50: 50 at T3 were tested. Stocking of Rohu were similar (2964/ha) for all the treatments. Similar stocking density (200564/ha) was maintained in all the treatments. The production obtained were 7138.30±63, 6977.75±78 and 7037.03±84 kg/ha from T1, T2 and T3 respectively. The highest production was obtained from T1 compared to other treatments. A straightforward economic analysis showed that treatment T1 (BCR -1.94, net profit: Tk.12,94,576/ha/6 months) had the highest benefit-cost ratio (BCR) and net profit, subsequent to treatment T3 (BCR -1.87, net profit: Tk.12,74,685/ha/6 months) and treatment T2 (BCR-1.93, net profit: Tk.12,02,956/ha/6 months). Therefore, it might be concluded that the species combination of pabda, gulsha and rohu followed by T1 may be a better option considering the production and economic benefits to farmer’s ponds in our country. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 219-228